The Role of Majelis Taklim Pitulasan and It’s Impacts on Women Spiritual Transformation at Kampung Magersaren Blitar - Abdul Rozak Ali Maftuhin; Saiful Amien; Moh. Nurhakim (Universitas Muhammadiyah Malang, 2025)
This study explores the role of Majelis Taklim Pitulasan in fostering women’s spiritual transformation in Kampung Magersaren, Blitar. The research adopts a qualitative approach using a case study method, with data collected through in-depth interviews, participant observation, and documentation. Data analysis was conducted using the Miles, Huberman, and Saldana model to ensure the validity and accuracy of the findings. The findings reveal that Majelis Taklim Pitulasan plays a significant role as a facilitator, motivator, and educator in enhancing the spirituality of its female members. The assembly reinforces religious discipline, such as consistent prayer practices, and provides psychological benefits, including increased inner peace and self-confidence. Furthermore, the fiqh al-nisā’ (women’s jurisprudence) studies delivered in the group have helped participants better understand and appreciate women’s roles in Islam. The assembly also contributes to building social solidarity through voluntary contributions and community-based activities that strengthen bonds among its members. This study affirms that non-formal religious education through majelis taklim has a transformative impact on women’s religious lives, both in ritual and social aspects. The findings underscore the importance of optimizing community-based learning methods to enhance the effectiveness of sustainable Islamic education.